Inhibitors of the interferon response enhance virus replication in vitro. - Claire E Stewart; Richard E Randall; Catherine S Adamson (PLoS ONE)
Virus replication efficiency is influenced by two conflicting factors, kinetics of the cellular interferon (IFN) response and induction of an antiviral state versus speed of virus replication and virus-induced inhibition of the IFN response. Disablement of a virus's capacity to circumvent the IFN response enables both basic research and various practical applications. However, such IFN-sensitive viruses can be difficult to grow to high-titer in cells that produce and respond to IFN. The current default option for growing IFN-sensitive viruses is restricted to a limited selection of cell-lines (e.g. Vero cells) that have lost their ability to produce IFN. This study demonstrates that supplementing tissue-culture medium with an IFN inhibitor provides a simple, effective and flexible approach to increase the growth of IFN-sensitive viruses in a cell-line of choice. We report that IFN inhibitors targeting components of the IFN response (TBK1, IKK2, JAK1) significantly increased virus replication. More specifically, the JAK1/2 inhibitor Ruxolitinib enhances the growth of viruses that are sensitive to IFN due to (i) loss of function of the viral IFN antagonist (due to mutation or species-specific constraints) or (ii) mutations/host cell constraints that slow virus spread such that it can be controlled by the IFN response. This was demonstrated for a variety of viruses, including, viruses with disabled IFN antagonists that represent live-attenuated vaccine candidates (Respiratory Syncytial Virus (RSV), Influenza Virus), traditionally attenuated vaccine strains (Measles, Mumps) and a slow-growing wild-type virus (RSV). In conclusion, supplementing tissue culture-medium with an IFN inhibitor to increase the growth of IFN-sensitive viruses in a cell-line of choice represents an approach, which is broadly applicable to research investigating the importance of the IFN response in controlling virus infections and has utility in a number of practical applications including vaccine and oncolytic virus production, virus diagnostics and techniques to isolate newly emerging viruses.